A Multi-Criteria Decision-Making Approach Using MOORA for Evaluating Job Search Platforms - Rogayah Rogayah; Ike Putri Kusumawijaya; Witta Listiya Ningrum (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
With the development of technology today, it can make it easier for many people to carry out various activities. For example, in searching for work using various job search websites. A job search website is one of the sites where there is an online platform opportunity that allows users to search for and apply for jobs that suit their qualifications and interests. This job search website also has the main aim of helping fresh graduates who have no experience in the field of work. However, this job search website has both positive and negative impacts. Therefore, applicants must first seek detailed information before applying for work. And you also have to look for a truly official platform to avoid fraud. The problems above can make applicants face difficulties in determining which is the best platform to meet their needs. So, to resolve the problems that occur in selecting a job search website, criteria data is really needed, including ease of use, ease of application, detailed information, speed of access, security, and number of site uses. So, a decision support system (DSS) is very necessary as a problem solving tool in selection of the best job search websites. In this research, the author applies the MOORA method to search for final results accurately and is assisted by using the ROC weighting method. Therefore, the one that gets the highest ranking in selecting the best job search website is an alternative. with value.